Identification of the predictors of preference for alfalfa hay by equines - Oliveira, Kátia De; Sá, Janaína Carolina De; Costa, Ciniro; Meirelles, Paulo Roberto De Lima; Fachiolli, Daniele Floriano; Pereira, Amanda Mantovani (UFBA - Universidade Federal da Bahia, 2018)
SUMMARY The purpose of this study was to identify predictors of preference for alfalfa hay by equines. A total of 15 quarter horses, at average age and body weight of 10 years and 500 kg were used, respectively. It was conducted an evaluation to identify the preference for alfalfa hay by horses by short-period tests of 10 min. This evaluation was conducted in pairs for each test hay (1-30), available on the market, against each standard (A, B, C), until the completion of all resulting combinations. Alfalfa hays classified as A, B and C, contained on average 22.88, 17.78 and 13.16% of crude protein, respectively. The evaluated variables were constituted by ethological, morphological, microbiological, bromatological and biological analysis. The horses showed a preference for the type A of alfalfa hay, followed by type B and C. The preference for alfalfa hay type A can be predicted by the equation:Pref . A = − 98.19 + 1.61 ( acid detergent fiber) + 1.53 ( in vitro dry matter digestibility ) + 18.54 ( stem thickness ) − 0.03 ( acid detergent fiber x in vitro dry matter digestibility ) − 0.02 ( acid detergent fiber x stem thickness ) − 0.28 ( in vitro dry matter digestibility x stem thickness ) , r 2 = 0.31 ,P = 0.0044. It was concluded that horses showed preference to alfalfa hay, wherein the best type A bales. Therefore to predict of preference of the equines for high quality alfalfa hay it's necessary to select bales with lower values of stem thickness and fiber in acid detergent, as well as presenting high level of dry matter digestibility.

RESUMO O objetivo com este estudo foi identificar preditores de preferência pelo feno de alfafa pelos cavalos. Foram utilizados 15 cavalos da raça quarto de milha, com idade média e peso corporal de 10 anos e 500 kg, respectivamente. Foi realizada uma avaliação para identificar a preferência pelo feno de alfafa por cavalos em testes de curto período de 10 min. Esta avaliação foi realizada em pares para cada teste de feno (1-30) em relação a cada padrão (A, B, C), até a conclusão de todas as combinações resultantes. As variáveis avaliadas foram constituídas por análises etológicas, morfológicas, microbiológicas, bromatológicas e biológicas. Os cavalos mostraram preferência pelo tipo A de feno de alfafa, seguido do tipo B e C. A preferência pelo tipo A do feno de alfafa pode ser predita pela equação:Pref . A = − 98.19 + 1 , 61( ADF ) + 1 , 53( IVDMD ) + 18 , 54( ST ) − 0 , 03( ADFxIVDMD ) − 0 , 02 ( ADFxST ) − 0 , 28( IVDMDxST ) , r 2 = 0,31 ,P = 0,0044. Concluiu- se que os cavalos mostraram preferência ao feno de alfafa, em que os melhores fardos do tipo A podem ser identificados selecionando-os porque eles contêm baixas quantidades de espessura do caule e fibra de detergente ácido, bem como altos níveis de digestibilidade da matéria seca in vitro.
Identificação dos preditores de preferência pelo feno de alfafa por equinos
Keywords: conserved forages; horses; Medicago sativa; palatability; forragem conservada; cavalos; Medicago sativa; palatabilidade